If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57 = 15 + -6x Solving 57 = 15 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 57 + 6x = 15 + -6x + 6x Combine like terms: -6x + 6x = 0 57 + 6x = 15 + 0 57 + 6x = 15 Add '-57' to each side of the equation. 57 + -57 + 6x = 15 + -57 Combine like terms: 57 + -57 = 0 0 + 6x = 15 + -57 6x = 15 + -57 Combine like terms: 15 + -57 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| 3r+24/9=5r-30/5 | | 1/3(12p+9)-(p-4) | | 4x/3(2x-4)=48 | | 3x-37=14 | | 1/2(12p+9)-(p-4) | | 3v+29=5v+7 | | 7x+6=26 | | 23-6x=-37 | | 2x+4(10-x)=28 | | -5x+2=-4(2y+4) | | 8n+62=13n+2 | | -7x-34=64 | | -9/4+8 | | 3x+12=93-6 | | -6x-16=-82 | | c+25=3c+1 | | -11+4x=19+2x | | 3/4*-3 | | -36-5=9-10x | | 90-7x= | | 9x-5(x-12)=30 | | 3/4*3 | | 3x+22=12x-58 | | 3x-8=x-8 | | 110-12x=266 | | 8x+9a-7b+9b-3a+12x= | | (7x+33)=(11x+21) | | 6x+35=15x-35 | | -31-3x=-73 | | x/9-x/10=11 | | 4x-3=14-73 | | 56-11x=166 |